2020
DOI: 10.1016/j.ijppaw.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

First identification and molecular phylogeny of Sparganum proliferum from endangered felid (Panthera onca) and other wild definitive hosts in one of the regions with highest worldwide biodiversity

Abstract: After decades of being neglected, broad tapeworms now attract growing attention thanks to the increasing number of reports from humans but also thanks to many advancements achieved by application of molecular methods in diagnosis and epidemiological studies. Regarding sparganosis, unfortunately general uniformity of most species, their high intraspecific variability and lack of agreement among researchers has led to confusion about the classification of Spirometra/Sparganum species. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…The high-quality reference genomes presented herein, however, provide valuable resources for further attempts to identify vestigial S. proliferum sequences in other organisms or to perform analyses of protein-protein interactions between hosts and parasites. Recently, a possible adult form of S. proliferum was isolated from wild felids and fragments of mitochondrial cox-1, nad-1 and atp-6 genes were sequenced 10 . Although those sequences showed higher similarities to S. proliferum than S. erinaceieuropaei or other tapeworms, the percentages of identities with the S. proliferum mitochondrion were relatively low (93% (320/343) in cox1, 96% (284/296) in nad1 and 92% (531/577) in atp6), suggesting they are closely related but not identical species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-quality reference genomes presented herein, however, provide valuable resources for further attempts to identify vestigial S. proliferum sequences in other organisms or to perform analyses of protein-protein interactions between hosts and parasites. Recently, a possible adult form of S. proliferum was isolated from wild felids and fragments of mitochondrial cox-1, nad-1 and atp-6 genes were sequenced 10 . Although those sequences showed higher similarities to S. proliferum than S. erinaceieuropaei or other tapeworms, the percentages of identities with the S. proliferum mitochondrion were relatively low (93% (320/343) in cox1, 96% (284/296) in nad1 and 92% (531/577) in atp6), suggesting they are closely related but not identical species.…”
Section: Discussionmentioning
confidence: 99%
“…However, the adult stage of S. proliferum has not been observed and the precise taxonomic relationships of S. proliferum with other worms remain unclear because most of the submitted sequences are of mitochondria origin and include only a limited number of genes. Recently, adult forms of tapeworms were isolated from wild felids and reported that they showed high-DNA sequence similarity to S. sparganum 10 . However, this study was based on only a few mitochondrial genes and more evidence is required to determine the precise taxonomic classification of this parasite.…”
mentioning
confidence: 99%
“…The occurrence of Spirometra infections across South America has been reported since the beginning of the 20th century [ 35 ]. This cestode has been previously recorded in Geoffroy’s cat ( Leopardus geoffroyi ), puma, and jaguarundi in western Paraguay [ 36 ]; the guiña ( Leopardus guigna ) in Chile [ 37 ]; and jaguar, puma, and margay ( Leopardus wiedii ) in Brazil [ 16 , 38 ]. Additionally, ocelots from Peru [ 39 ] and Brazil [ 38 ] have been shown to represent feasible definitive hosts of Spirometra sp.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, the presence of metazoan parasites has also been reported in non-domestic NWF, showing them as feasible hosts of gastropod-borne metastrongyloid lungworms [ 11 , 12 ] or Dirofilaria immitis , the causative agent of heartworm disease [ 13 ]. Other helminths, for instance, hookworms [ 14 ], trematodes [ 15 ], and cestodes, [ 13 , 16 , 17 , 18 ] have also been reported in non-domestic wild felids as well as ectoparasites like ticks, mites, and fleas [ 19 ]. The sophisticated ways in which parasite life cycles have evolved to ensure transmission involve complex interactions with vertebrate and invertebrate hosts, and parasite assemblage reflects the host’s trophic position within the food web [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other clade among S. decipiens complex 1 was formed with Spirometra retrieved from wild felids, L. munoai, P. concolor and L. pardalis (these two latter from Argentina) [27]. Although Arrabal et al [27] registered diphyllobothriideans adults and eggs as Sparganum proliferum, this is the denomination for a larval stage; consequently, the adult stage and its products (eggs) should be named as Spirometra sp. Phylogenetically, this taxon seemed to be closer to Spirometra sp.…”
Section: Discussionmentioning
confidence: 99%